2017
DOI: 10.18287/jbpe17.03.030501
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Poincaré Plots as Descriptors of Speckle Pattern Second-Order Statistics

Abstract: Abstract. It is demonstrated herein that the use of spatial Poincaré plots provides an efficient means to describe short and long-range correlations in the spatial structure of the measured intensity distribution of scattered coherent fields. The intensity distribution over a row of pixels in single frames of speckle fields with varying speckle sizes was considered. Statistical descriptors from the spatial Poincaré plots for these intensity data with variable lags were used to estimate the short and long-term … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…A change in wavelength on a scale below the speckle correlation limit causes only grain-scale changes to the speckle pattern. Recently, a technique involving Poincaré descriptors was developed to investigate the size of speckle grains [19,20]. Here we show that the grain-scale variations of speckle patterns that are induced by changes of the wavelength λ are also captured by a Poincaré descriptor.…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…A change in wavelength on a scale below the speckle correlation limit causes only grain-scale changes to the speckle pattern. Recently, a technique involving Poincaré descriptors was developed to investigate the size of speckle grains [19,20]. Here we show that the grain-scale variations of speckle patterns that are induced by changes of the wavelength λ are also captured by a Poincaré descriptor.…”
Section: Introductionmentioning
confidence: 72%
“…This Poincaré descriptor is otherwise known as the standard deviation of lag-k differences, related to the standard deviation of successive differences [21], which is widely used in areas such as heart rate variability analysis [22,23]. It was recently demonstrated that this met-arXiv:1909.00665v1 [physics.optics] 2 Sep 2019 ric can probe short-range correlations in the spatial and temporal structure of speckle [19,20]. In order to track grain-scale changes of speckle patterns, we set the parameter k to the size of a typical speckle in the image, determined using the methods outlined in [19].…”
Section: Poincaré Descriptor For Wavelength Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…Either approach yields the same information as the autocorrelation function and the PWD constitute a Fourier transform pair. An alternative approach of using spatial Poincaré plots with variable lag lengths was recently presented by Majumdar and Kirkpatrick [15]. This approach reduces some of the uncertainties associated with the approaches discussed above, particularly as the speckle size gets large and also provides a more physical connection with speckle size and the correlation length of the intensity pattern.…”
Section: Second Order Statisticsmentioning
confidence: 99%
“…When the speckle size equaled 2 pixels, the spatial Nyquist criteria was met [13]. This process for generating synthetic speckle patterns has been used extensively in the past [2,6,12,[13][14][15]. Using these speckle patterns, the effects of the neighborhood size over which speckle contrast was calculated was investigated as a function of speckle size and the results compared to those obtained when the sampled intensities were statistically independent from each other.…”
Section: Laser Speckle Numerical Simulationmentioning
confidence: 99%